A triple threat: high population density, high foraging intensity and flexible habitat preferences explain high impact of feral cats on prey. Issue 1942 (13th January 2021) - Hamer, Rowena P.; Gardiner, Riana Z.; Proft, Kirstin M.; Johnson, Christopher N.; Jones, Menna E.
Abstract : Alien mammalian carnivores have contributed disproportionately to global loss of biodiversity. In Australia, predation by the feral cat and red fox is one of the most significant causes of the decline of native vertebrates. To discover why cats have greater impacts on prey than native predators, we compared the ecology of the feral cat to a marsupial counterpart, the spotted-tailed quoll. Individual prey are 20–200 times more likely to encounter feral cats, because of the combined effects of cats' higher population densities, greater intensity of home-range use and broader habitat preferences. These characteristics also mean that the costs to the prey of adopting anti-predator behaviours against feral cats are likely to be much higher than adopting such behaviours in response to spotted-tailed quolls, due to the reliability and ubiquity of feral cat cues. These results help explain the devastating impacts of cats on wildlife in Australia and other parts of the world.